’Typical of Her Race’: Cultural Pluralism and the Editorial Records of Survey Graphic - Johnson, Bob (American Studies, 2012)
This article reconstructs the editorial politics of early cultural pluralism by examining the records of the progressive magazine The Survey and its illustrated monthly edition Survey Graphic. By following several behind-the-scenes discussions among editors, contributors, and readers of the magazine’s special Race Series (which included the famous 1925 "Harlem: Mecca of the New Negro" edition), it sheds light on both the racial unconscious of early cultural pluralism, as evident in editorial discussions, and the complex and often tortured representational politics of the pluralist project at the magazine. The article turns specifically to editorial correspondence concerning special editions of the magazine that were dedicated to the European gypsy, the so-called New Negro, and the New Immigrants.